2018
DOI: 10.1111/jgh.14447
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of elbasvir/grazoprevir for Japanese patients with genotype 1b chronic hepatitis C complicated by chronic kidney disease, including those undergoing hemodialysis: A post hoc analysis of a multicenter study

Abstract: The present study demonstrated that elbasvir and grazoprevir are highly effective and safe for genotype 1b chronic hepatitis C Japanese patients with CKD, including those undergoing hemodialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 45 publications
4
28
0
Order By: Relevance
“…This finding was comparable with recent publication in Japan, 15 and an SVR12 rate of 100% was established in this subgroup.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding was comparable with recent publication in Japan, 15 and an SVR12 rate of 100% was established in this subgroup.…”
Section: Discussionsupporting
confidence: 93%
“…There was no significant statistical difference between cirrhosis and noncirrhosis during the course of treatment or follow‐up period (Figure ). This finding was comparable with recent publication in Japan, and an SVR12 rate of 100% was established in this subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…SVR12 rates remained high across other important participant subgroups, including those with compensated cirrhosis, with a baseline viral load > 2 000 000 IU/mL, and aged ≥ 65 years, but SVR12 was lower in participants with GT1a infection. These data support the findings from the EBR/GZR phase 3 clinical development program in both Asian and white individuals and are also consistent with several recent studies reporting SVR rates of 94–98% in Japanese individuals with HCV GT1 infection following treatment with EBR/GZR …”
Section: Discussionsupporting
confidence: 91%
“…These data support the findings from the EBR/GZR phase 3 clinical development program in both Asian and white individuals and are also consistent with several recent studies reporting SVR rates of 94-98% in Japanese individuals with HCV GT1 infection following treatment with EBR/GZR. [22][23][24] Non-structural protein 5A RASs at amino acid positions L31 and Y93 were common among the 12 participants with HCV GT1b infection who experienced relapse, and in most of these participants, the RASs remained detectable at the time of virologic failure. Among the small number of participants with relapse who had GT1b infection and wild-type virus at baseline, all had treatment-emergent Y93H at the time of failure.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, interferon‐free, direct‐acting antiviral treatment is the standard of care for chronic hepatitis C, and yields a high sustained virologic response rate . Several phase 3 and real‐world studies have demonstrated that the following direct‐acting antiviral treatment regimens are effective and safe, even for chronic kidney disease patients with and without haemodialysis: daclatasvir/asunaprevir, ombitasvir/paritaprevir plus ritonavir, and grazoprevir/elbasvir . However, these regimens have some limitations.…”
Section: Introductionmentioning
confidence: 99%